Elliptical restoration based single-phase dynamic voltage restorer for source power factor correction - Ye, Jian (2020)
The dynamic voltage restorer (DVR) can compensate the load voltage by injecting a series voltage in the distribution line. However, the conventional compensating methods only focus on the load voltage and the DVR itself. The power factor correction (PFC) at the source side has seldom been considered. This paper aims at correcting the power factor (PF) at the source side using an elliptical restoration based voltage compensating method via the single-phase dynamic voltage restorer (DVR). Specifically, the virtual impedance is used to describe the active and reactive components of the DVR injected voltage. The active and reactive voltage components and a centrifugal angle are utilized to formulate an elliptical compensation trajectory. When the centrifugal angle changes from 0° to 90°, the injected voltage will follow the elliptical compensation trajectory. Thus a smooth changeover of the DVR injected voltage can be achieved during the load switching. The source voltage will be in phase with the load current with the proper control of the DVR injected voltage. It means that the PFC at the source side can be achieved using the proposed compensating method. A laboratorial prototype of the single-phase DVR is utilized to validate the proposed control method. The experimental results verify that a unity PF can be maintained at the source side with seamless state transition.